Contribuição ao conhecimento de Macoma (Austromacoma) constricta (Bruguière, 1792) (Bivalvia, Heterodonta, Tellinidae) - Geraldes, Inês Lepore Ferreira (1982)
Studies on marine bivalves of the Subfamily Macominae Olsson, 1961, the characterization of the major groups, from subclass to subfamily, is presented in order to place the refered subfamily among the Bivalvia. Characterization, as well as geological and geographic distribution, is presented for the genera and subgenera, along with general considerations and illustrations of the shells of the species occuring on the Brazilian coast. ln relation to Macoma (Austromacoma) constricta (Bruguière, 1792), a recente species which occurs from North Carolina (USA) to Rio Grande do Sul (Brazil), detailed studies were developed based both in the material examined and in the bibliography. These studies comprised: taxonomy, anatomical and microanatomical remarks, comments on ciliary currents in the mantle, data related to the collecting site (Praia do Carbo, Baía de Sepetiba, RJ), and observations of the animal in aquarium.